Prevalence of brain death in patients coming from the urgency and emergency sector (Research, Society and Development, 2024)
Objective: To identify the prevalence of brain death in patients admitted to the hospital service through the urgent and emergency sectors of two hospitals in Paraná, one public and the other mixed. Methods: This is an exploratory, documentary, descriptive, field, cross-sectional, retrospective, and quantitative profile research, to be carried out through medical records, to identify the prevalence of BD in patients coming from the emergency department of two reference hospitals for trauma and neurology care, from 2019 to 2023. Results: This research identified that the profile of potential donors was men, aged between 40 and 60 years old, admitted predominantly for traumatic and vascular causes, diagnosed with traumatic brain injury and stroke. It was found that the number of effective transplants is considerably lower when compared to the prevalence of notifications, highlighting that the main causes for non-donation are family refusal and the patient's unwillingness to live. Conclusion: It is noteworthy that over the years, organ transplants have increased considerably, especially in the state of Paraná. This fact may be related to the understanding of the subject due to the greater number of campaigns, highlighting the importance of more research in the area.